2018
DOI: 10.1016/j.breast.2017.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of immediate versus delayed breast reconstruction: Results of a multicenter prospective study

Abstract: Background Previous studies suggest that immediate reconstruction following mastectomy produces superior results over delayed procedures. However, for medical or oncological reasons, some patients may be poor candidates for immediate reconstruction. We compared complications and patient-reported outcomes between immediate and delayed breast reconstructions in a prospective, multicenter study. Methods 1957 patients (1806 immediate, 151 delayed) met eligibility criteria. Demographic data, major complications, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
134
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(146 citation statements)
references
References 47 publications
10
134
1
1
Order By: Relevance
“…Immediate breast reconstruction has become the preferred reconstructive approach for women with breast cancer. According to the literature, more than 70% of breast reconstructions are performed at the time of mastectomy [6], for several reasons. Studies have shown that IBR is oncologically safe [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Immediate breast reconstruction has become the preferred reconstructive approach for women with breast cancer. According to the literature, more than 70% of breast reconstructions are performed at the time of mastectomy [6], for several reasons. Studies have shown that IBR is oncologically safe [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research studies have focused on optimizing PMRT delivery by assessing the timing of reconstruction in relation to PMRT, [9][10][11] the best type of reconstruction, 12,13 and advances in planning and PMRT delivery. 2 However, aspects of PMRT techniques, such as using chest wall boost (CWB), which is delivered to the mastectomy chest wall or scar with the aim of improving local tumor control, have yet to be explored in the setting of breast reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…cases. [8][9][10] The percentage of mutation carriers who decide to undergo prophylactic bilateral mastectomy differs between countries.…”
mentioning
confidence: 99%